Correlation between smoking and anthropometric variables in blood donors in Piauí - doi:10.5020/18061230.2010.p11 - França, Júlio César Queiroz de (2012)
Objective: To assess the relationship between smoking, body weight and body fat distribution of blood donors in Piaui. Methods: A cross-sectional study with a sample of 595 blood donors, regardless of sex, from 18-61 years, registered at the Center for Hematology of Piauí (HEMOPI). Data were collected from November/2008 to February/2009. Cigarette consumption was assessed through an informed questionnaire. The measurements taken were: weight, height, waist and hips. We assessed the body mass index (BMI), waist circumference (WC) and waist-hip ratio (WHR). The group was divided into three subgroups (smokers, nonsmokers and former smokers) by the presence or absence of smoking practice. The association between variables was assessed by applying the Mann-Whitney/Wilcoxon test adopting the value of p 0.05 for significance. Results: Waist circumference and waisthip ratio were found positively associated only in females, both to current smoking practice (p = 0.0196 and p = 0.0050, respectively) as to the former (p = 0.0167 and p = 0.0167, respectively). Among smokers, the quantity of cigarettes smoked per day was positively associated with BMI in males (p = 0.0179) and WHR in females (p = 0.0448). Conclusion: Cigarette smoking, particularly among females, was associated with body fat distribution